Optical ray tracing-guided myopic laser in situ keratomileusis: 1-year clinical outcomes - Cummings AB (Dove Medical Press, 2013)
Arthur B Cummings,1 Gabrielle E Kelly21Wellington Eye Clinic, Dublin, Ireland; 2School of Mathematical Sciences, University College Dublin, Dublin, IrelandPurpose: To compare the safety, efficacy, and predictability of laser in situ keratomileusis treatments at 1 year postprocedure using a novel geometric ray tracing algorithm with outcomes of treatments using wavefront-optimized, wavefront-guided, and topography-guided ablation profiles of an excimer laser (WaveLight GmbH, Erlangen, Germany; Alcon Laboratories, Fort Worth, TX, USA).Setting: Wellington Eye Clinic, Dublin, Ireland.Design: Retrospective comparative case series.Methods: Eyes having a preoperative myopic spherical equivalent refractive error >4.00 D and/or astigmatism between 2.00–6.00 D resulting in a spherical equivalent power greater than −4.00 D received laser in situ keratomileusis treatments using a ray tracing algorithm. Refractive outcomes were analyzed postoperatively at 6 and 12 months and were compared to outcomes of wavefront-optimized, wavefront-guided, and topography-guided treatments in eyes with the same pretreatment refractive range.Results: Forty-seven eyes of 26 patients were treated using the ray tracing algorithm. At 12 months postprocedure, uncorrected visual acuity was better than the preoperative best-corrected visual acuity in this group. The percentage of eyes achieving an uncorrected visual acuity or best-corrected visual acuity ≥20/20 significantly exceeded the rates achieved in the wavefront-optimized and topography-guided groups. A greater percentage of eyes achieved an uncorrected visual acuity ≥20/20 and ≥20/16 in the wavefront-guided group, but no eyes in the wavefront-guided group had an uncorrected visual acuity ≥20/12.5 in comparison to 9.5% of eyes in the ray tracing group.Conclusion: This study provides further evidence of the safety, efficacy, and predictability of laser in situ keratomileusis outcomes using an optical ray tracing algorithm to treat moderate to high myopic astigmatism and shows that good results are sustained through 1 year.Keywords: LASIK, optical ray tracing, wavefront-guided, wavefront-optimized, topography-guided, ablation profiles, Gullstrand eye model